Sensitivity of macroinvertebrates to carbendazim under semi-field conditions in Thailand: Implications for the use of temperate toxicity data in a tropical risk assessment of fungicides - Daam, MA
The present paper discusses the fate of the fungicide carbendazim (nominal concentrations: 0, 3.3, 33, 100 and 1000 mu g L(-1)) and its effects on the macroinvertebrate community in outdoor microcosms set up in Thailand. Fate and threshold values were subsequently compared with those noted in temperate model ecosystem studies in order to evaluate to which extent toxicity data generated in temperate regions for compounds like carbendazim may be extrapolated to tropical areas. Carbendazim disappeared faster from the water column than reported in temperate model ecosystem studies, which is explained by a possibly greater microbial breakdown of the fungicide under the tropical conditions tested. The No Observed Effect Concentration (NOEC) calculated in the present study for the macroinvertebrate community was the same as recorded in a study carried out in The Netherlands (3.3 mu g L(-1)). However, most sensitive representatives in the latter study were "worm-like" taxa, whereas water boatmen (Corixidae) were the most sensitive macroinvertebrates in the present study. The ecological realism of a tropical risk assessment based on temperate organisms that are less sensitive than local macroinvertebrates may be questionable. Recommendations for future research include testing the possibility to rear sensitive representatives of indigenous Thai Corixidae in the laboratory and conducting model ecosystem studies evaluating a wider range of pesticides on a larger tropical geographical scale. (c) 2008 Elsevier Ltd. All rights reserved.